Privatisation of public listed companies from Bursa Malaysia: corporate governance and financial characteristics - Sazali, Saad (2021)
Public listed company (PLC) status provides many benefits to companies to expand and grow. Even though the companies have already achieved PLC status, many factors influence the decision to go private. Interestingly, many delisted companies from the stock exchange were well-established companies. Their decision to go private provided a dramatic impact on Bursa Malaysia. Because of that, the decision to convert a public listed company into a privatised entity becomes a big decision that must be considered in dealing with the new compliance requirements and investors dissatisfaction. Therefore, this study aims to identify the factors that influence the privatisation of public listed companies in Malaysia. A logistic regression model was used to test the hypotheses. Delisted company data were collected from 2005 to 2015, involving 115 companies. Annual reports of these companies were collected for the last three years prior to being delisted from Bursa Malaysia. A matching procedure was made with a matching listed company based on same asset size in the same industry. Overall, 690 data on corporate governance and financial characteristics from the three-year periods were collected. Out of 18 hypotheses tested, ten hypotheses were supported which indicate that privatisation of PLC is influenced by board of directors’ size, number of meetings, family ownership, institutional investors, foreign investors, substantial investors, leverage, growth opportunity, audit fees, and nonaudit fees. Meanwhile, eight hypotheses were not supported (proportion of independent directors, CEO duality, director’s shareholding, free cash flow, dividend per share, market value to book value, ROA, and ROE) by the results. The outcome of this study is expected to enrich understanding and conception of the effective factors on privatisation and be used as a guide for practitioners, regulators, and policymakers to strengthen the mechanism of privatisation of PLCs in Malaysia.